INDEKS ENTOMOLOGI DAN SEBARAN VEKTOR NYAMUK Aedes spp DI KELURAHAN PINANG KENCANA KECAMATAN TANJUNGPINANG TIMUR KOTA TANJUNGPINANG, KEPULAUAN RIAU: Entomology Index and Aedes Spp Mosquito Vector Distribution in Kelurahan Pinang Kencana Sub-District Tanjungpinang Timur City of Tanjungpinang, Riau Island - susanti, Yuni; Kurnia, Risman; Pitriyanti, Luh (Poltekes Kemenkes Tanjungpinang, 2022)
Dengue hemorrhagic fever (DHF) is a disease that is still a health problem in Indonesia caused by the dengue virus and is transmitted through the Aedes spp mosquito as the main vector that causes this disease. Tanjungpinang Timur District since January-December 2020 in the Pinang Kencana Village has recorded 52 positive right. The type and design of this study used observational research by conducting a descriptive analysis survey with a cross sectional study approach, the variables studied were the entomological index and the distribution of the Aedes spp mosquito vector. How to collect data by surveying larvae and taking the coordinates of the houses of DHF sufferers and their surrounding houses. The results of this study show that as many as 100 houses were surveyed, the House Index (HI) was 28%, the Container Index (CI) was 14% and the Breteau Index (BI) was 33%. The distribution of the presence of Aedes spp mosquito larvae is based on the coordinates of the house of dengue cases adjacent to the positive house of Aedes spp mosquito larvae in Pinang Kencana Village, Tanjungpinang Timur District. The conclusion of this study, based on the results of the entomological index, obtained a Density Figure (DF) in Pinang Kencana Village with a medium density category. Suggestions for the community to more attention cleanliness of controllable containers. Containers are most found larvae is bucket containers inside house and bottle containers outside house. Suggestions for health agencies can be a reference in vector control and can further mobilize Mosquito Nest Eradication (MNE) and 3M Plus in Pinang Kencana Village, Tanjungpinang Timur District.